2021
DOI: 10.1007/978-3-030-78288-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Hybrid Model for the Diffusion of Innovation in Energy Communities

Abstract: The need for comprehensive models to simulate the diffusion of innovations in communities or social systems has become eminent. Existing models such as the Diffusion of Innovation expound how ideas, products, or innovations gain acceptance and spread over time. Other analogous models, such as the Transtheoretical Model also claim that people do not change behaviours quickly and decisively. Instead, they change in a continuous and cyclical process of internal decision-making. Although these two models are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…While this is a single example among many, the general observation for almost all the cases discussed in [ 15 ] seems to follow a similar or common trend in terms of composition, thus having multiple and autonomous actors, heterogeneity of actors, relationships between actors, and ownership of different kinds of energy resources. The types of ownership were wide-ranging, and the kinds of governance systems were also diverse.…”
Section: Background Knowledge and Conceptsmentioning
confidence: 88%
See 2 more Smart Citations
“…While this is a single example among many, the general observation for almost all the cases discussed in [ 15 ] seems to follow a similar or common trend in terms of composition, thus having multiple and autonomous actors, heterogeneity of actors, relationships between actors, and ownership of different kinds of energy resources. The types of ownership were wide-ranging, and the kinds of governance systems were also diverse.…”
Section: Background Knowledge and Conceptsmentioning
confidence: 88%
“…As mentioned at the beginning of this section, the result of a case study conducted in [ 15 ] is adopted here to shed further light on the assertion that these energy ecosystems are usually comprised of multiple, autonomous, and heterogeneous actors who happen to share a common environment and engage with each other in some form of interactions or relationships. From the many cases considered in the study, we borrowed the case of Feldheim [ 26 ], which is located in Germany, and shown in Table 1 .…”
Section: Background Knowledge and Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…While various management strategies such as microgrids [7], [8], improving the integration of renewable sources into the power grid [9] and others have been discussed in the literature, various other studies, including [10] and [11], further highlighted the potential role of the "Collaborative Virtual Power Plant Ecosystem" (CVPP-E) and the "Cognitive Household Digital Twin" (CHDT) concepts as promising constructs for improving energy use in these households, helping to reduce the greenhouse gas emission problems that currently threaten the planet. In [10] and [11] the authors envisioned that these concepts could have a significant role in the implementation of Renewable Energy Communities (RECs), as well as the Smart City concept. Building on these concepts, a renewable energy community can be described as an ecosystem composed of various prosumers who have a photovoltaic system installed on the roof of their homes, and consumers who do not have this system.…”
Section: Introductionmentioning
confidence: 99%